Effects of elevated C[O.sub.2] and temperature on the growth, elemental composition, and cell size of two marine diatoms: potential implications of global climate change - Tew, Kwee Siong; Kao, Yu-Chen; Ko, Fung-Chi; Kuo, Jimmy; Meng, Pei-Jie; Liu, Pi-Jen; Glover, David C (Hydrobiologia, 2014)
Two pennate diatoms, Amphora coffeaeformis and Nitzschia ovalis, were used to evaluate potential responses to the future C[O.sub.2] and temperature increases with respect to cell-specific growth rate, elemental composition, size, population growth rate, and carrying capacity. Diatoms were subjected to four different treatments over a 2 week period (approximately 4 generations): a control (28°C and present-day C[O.sub.2], ~400 ppm), high C[O.sub.2] (28°C with high C[O.sub.2], ~750 ppm), high temperature (31°C and present-day C[O.sub.2], ~400 ppm), and greenhouse-effect treatment (31°C with high C[O.sub.2], ~750 ppm). The results indicated that both the cell-specific growth rates and the carrying capacity of A. coffeaeformis decreased at the higher temperature treatment, whereas N. ovalis did not differ among all treatments. No significant difference was found in either species' elemental cell composition, but higher C:N and C:P ratios were observed for A. coffeaeformis and N. ovalis, respectively, in high C[O.sub.2] and greenhouse-effect treatments. Smaller cell sizes were observed for both species under the greenhouse-effect treatment, a phenomenon that could alter benthic food webs in the future.